Symbiotic Bonding between Land and Human Beings in Willa Cather’s O Pioneers! - Dhami, Prem Bahadur (Patan Pragya, 2020)
This paper explores the symbiotic bonding between land and human beings in the novel. Writer chooses Carther’sO Pioneers! being ecologically conscious text when it is read against the background of deep Ecology. Writer finds this text that expounds upon the symbiotic bonding between land and human beings to subvert anthropocentric notion and its constraints. Clinging with the ideas why many critics and writers focused this text against the grain of ecocritical perspective, writer here tries to bring the balance in literary components and ethics of the discipline with the perspective of Leopold’s deep ecology and its components. Overall, writer tries to analyse how this text show the eco-consciousness perspectives avoiding the one-dimensional approach that reads culture and nature to revitalize literary study and help address some of the pressing questions concerning our global and local ecology. The characters, setting, and the plot of the novel show the biorhythm with nature. This is argued on basis of various ecocritics; Aldo Leopold’s concept of The Land Ethic, Scott Russell Sanders, John Hannigan, Glotfelty Cheryll, David Pepper and Holmes Rolston III on the interplay between nature and human beings.